PEMBUATAN ALAT PENGUKUR TINGGI BADAN OTOMATIS BERBASIS ARDUINO - Bakri, Muhammad Amin; Paridawati, Paridawati; Sikki, Ilyas; Handoyo, Yopi; Sylviana, Rika; Surahto, Aep; Diningrum, Jenny Primanita; Liliani, Netta; Syahputra, Novin; Asrika, Sukwati Dewi; Apriliansyah, Mario (LPPM Universitas Islam 45 Bekasi, 2022)
The facilities used by Posyandu cadres in weighing and measuring the height of children under five are not sufficient, because apart from that, they are not feasible nor are they calibrated accurately. Especially for measuring the height of toddlers, so far the posyandu generally still use the manual method, Based on this background, a digital height measuring device was designed in order to refer to the mission of the Unisma Bekasi Faculty of Engineering in an effort to increase the quantity and quality of community service (PPM) in the field of applied technology (appropriate technology), so this program was implemented. The PPM partners targeted for this program are Posyandu Kemuning cadres, Jatirasa Village, Jatiasih District, Bekasi City. The results of the design of this tool complete the automatic height measurement which is quite satisfactory at the Kemuning Posyandu, Jatirasa Village, Jatiasih District, Bekasi City. Development of a baby height and body mass measurement tool based on the ATmega 8535 microcontroller by utilizing a phototransistor sensor.